CONTENT OF BIOLOGICALLY ACTIVE SUBSTANCES OF PHENOLIC NATURE OF SOYBEAN (GLYCINE MAX (L.) MERR.) FOR THE ACTIONS OF NON-IONIC COLLOIDAL SOLUTIONS OF NANOPARTICLES OF METALS - Ситар, О. В.; Новицька, Н. В. (Scientific Progress & Innovations, 2014)
In the article the results of research on the impact of pre- treatment of soybean seeds with solutions of metal nanoparticles to regulate its biochemical composition as a source of pharmacologically important compounds of phenolic nature. The positive effect of soybean processing non-ionic colloidal solutions of nanoparticles from silver, molybdenum, manganese and iron content to increase leykoantotsianiv, isoflavones and polyphenols in soybean seeds. In particular, pre-treatment of non-ionic colloidal solutions of metal nanoparticles on the basis of silver, molybdenum, manganese and iron content boosted leucoanthocyanins, isoflavone content increased on average by 30% relative to control.